Intercorrências perinatais em indivíduos com transtorno invasivos do desenvolvimento - Sanches, Cristiane Prugovechi (2010)
Pervasive Developmental Disorders (PDD) are complex developmental multifactorial disorders with high rate of herdability. In this context, prenatal and perinatal risk factors also have been documented, such as maternal and fetal hypotiroidism, fetal exposition to alcohol, thalidomide; misoprostol and valproic acid, MMR vaccine among others. Epidemiological prospective studies accumulate evidences suggesting that advanced parental age; obstetric complications and intrapartum hypoxia are the main risk factors. Clinical and experimental evidences points out that if the fetus is exposed to antenatal maternal stress the child are more likely to have developmental problems including the autism spectrum disorders phenotype. This study evaluated the frequency of 50 perinatal complications and 36 psychological stressors in 44 pregnancies of the 19 PDD patient´s mothers. All the subjects were assisted at APAE from the Barueri municipality in the State of São Paulo. The main results of the study were: a) lower mean maternal and paternal age among non-PDD pregnancies; b) 19% and mean of 9,4 perinatal complications in PDD gestations versus 14,6% and mean of 7,5 for non-PDD gestations; c) more CNS insults among PDD gestations; d) expressive occurrence of psychological stressors in the life of these women, in PDD gestations or not; e) increased psychological stressors number in PDD gestations. There was no statistically significance in the pointed differences.